Unsteady Gaseous Poiseuille Slip Flow in Rectangular Microchannels - Siginer, D (Springer Verlag, 2019)
Unsteady slip flow of an incompressible gaseous fluid in a rectangular microchannel subject to a sudden time-dependent pressure drop is investigated via the generalized integral transform method. Three novel analytical solutions of the governing partial differential equations corresponding to first- and second-order slip models are derived. These can be used in the experimental determination of the constant slip length for any fluid–solid combination. All unsteady flow patterns asymptotically reach the fully developed state for each problem considered in the present investigation. © 2019, The Brazilian Society of Mechanical Sciences and Engineering.